Upaya Supervisi Kepala Sekolah Untuk Meningkatkan Mutu Pembelajaran Di SMK NU Kaplongan - Lisyanti Lisyanti; Titin Suprihatin; Trisna Trisna (LPPM Bunga Bangsa Cirebon, 2021)
Research in the field that the supervision carried out by the principal in improving the quality of teacher learning on the indicators of coaching starts from planned recruitment. Recruitment is carried out as input for qualified teachers. Strategies in improving the quality of teacher learning are carried out in collaboration with the industrial world so that knowledge and technical abilities can be increased to increase competitiveness. Monitoring indicators are carried out by monitoring teacher performance by making visits to each class on a scheduled basis to see the presence of teachers in theory classes and practical classes to ensure the continuity of the teaching and learning process according to the planned schedule. In the evaluation indicator, teacher performance evaluation is carried out every year using a special tool for teacher performance assessment. If the performance is considered good, then they are allowed to continue teaching and are given additional hours/performance bonuses, if the performance is poor, they are given coaching in the form of reduced hours so that they are not given teaching hours. The results of the comparison with Singapore's ITE College Center schools are the same both through coaching, monitoring, and evaluation.. Abstrak Penelitian di lapangan bahwa supervisi yang dilakukan kepala sekolah dalam peningkatan mutu pembelajaran guru pada indikator pembinaan dimulai dari rekruitmen yang terencana. Rekruitmen dilakukan sebagi input guru yang berkualitas. Strategi dalam peningkatan mutu pembelajaran guru dilakukan melalui kerja sama dengan dunia industry sehingga pengetahuan dan kemampuan teknis dapat meningkat untuk meningkatkan daya saing. Pada indikator pemantauan dilakukan dengan Pemantauan terhadap kinerja guru dengan melakukan kunjungan ke tiap kelas secara terjadwal untuk melihat keberadaan guru di dalam kelas teori dan kelas praktik untuk memastikan keberlangsungan proses belajar menagajar sesuai jadwal yang direncanakan. Pada indicator evaluasi yaitu evaluasi kinerja guru dilakukan setiap tahun dengan menggunakan perangkat khusus penilaian kinerja guru. Apabila kinerjanya dinilai baik maka dibiarkan untuk lanjut mengajar dan diberi tambahan jam/bonus kinerja, kalau kinerjanya buruk maka diberi pembinaan berupa pengurangan jam hingga tidak diberi jam mengajar. Hasil komparasi dengan sekolah ITE College Centre Singapura terdapat hal yang sama baik melalui pembinaan, pemantauan, dan evaluasi.